Revolutionising Tourism Accessibility for The Deaf and Hard of Hearing with XR Technology - Mohd Harith Syazwan, Samsawi; Suriati Khartini, Jali; Mohamad Imran, Bandan; Syahrul Nizam, Junaini; Sylvester, Arnab; Phei Chin, Lim; Kuryati, Kipli; Sarni Suhaila, Rahim (Pejabat Karang Mengarang (UPSI Press), Universiti Pendidikan Sultan Idris., 2025)
Extended Reality (XR) technology has emerged as a powerful tool for enhancing accessibility and inclusiveness across various industries, including tourism. Despite technological advancements, deaf and hard-of-hearing individuals continue to face significant challenges in fully engaging with tourism experiences due to communication barriers and the lack of tailored accommodations. This systematic review explores the potential of XR technologies to improve accessibility for this community, evaluates their effectiveness in addressing existing challenges, and examines their impact on travel experiences. A total of 16 studies were identified through a keyword search in the Scopus and Web of Science databases. The review analyses research methodologies, types of XR technologies utilised—including Virtual Reality (VR), Augmented Reality (AR), and Mixed Reality (MR)—and the advantages and limitations of their implementation. Findings suggest that XR can bridge communication gaps by providing immersive sign language translations, real-time captioning, and interactive visual guides, thereby enabling more engaging, informative, and independent tourism experiences for deaf and hard-of-hearing travelers. However, challenges such as high development and implementation costs, usability concerns, and the absence of standardised guidelines limit widespread adoption. This review highlights the need for user-centred design, active collaboration with the deaf and hard-of-hearing community, and further empirical studies to validate XR solutions. Future research should focus on improving long-term user engagement, enhancing the usability of XR applications, and expanding their integration across different tourism sectors. By addressing these gaps, XR technology can contribute to a more inclusive, accessible, and immersive tourism landscape for all travelers.